When disease extent is not always a key parameter: Management of refractory ulcerative proctitis - Georgios Michalopoulos; Konstantinos Karmiris (Elsevier, 2022)
Αbstract: Background: Patients with ulcerative proctitis represent a sub-group of ulcerative colitis patients with specific characteristics. Disease-related symptoms, endoscopic findings and patient's personality perspectives create a difficult-to-assess condition in certain cases. Objectives: To summarize available evidence on the management of refractory ulcerative proctitis and provide insights in treatment options. Results: /Conclusion: Topical therapy plays a central role due to the location of the disease. However, well-established treatment options may become exhausted in a considerable proportion of ulcerative proctitis patients, indicating the need to advance to more potent therapies in order to induce and maintain clinical response and remission in these refractory cases. Systemic corticosteroids, thiopurines, calcineurin inhibitors, biologic agents and small molecules have all been tested with variable success rates. Investigational interventions as well as surgical procedures are kept as the ultimate resort in multi-treatment resistant cases. Identifying early prognostic factors that herald a disabling disease progression will help in optimizing treatment and avoiding surgery.